Ectoparasites of bats and rodents in Mt. Kimangkil, Bukidnon - Dangcogan, Sherwynn B. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 1998)
Ectoparasites of bats and rodents collected in Mt. Kimangkil, Bukidnon were identified. To gather ectoparasites of bats and rodents, actual searching and direct examination of the host, clothbags and trays were made. Bats were found to harbor four families of ectoparasites, namely; Myobiidae, Nycteribiidae, Spinturmicidae, and Streblidae. Three families of ectoparasites namely; Haematopinidae, Ixodidae, and Pulicidae were found in rodents. Results showed the Family Nycteribiidae was the most abundant in bats while Haematopinidae and Ixodidae in rodents. The ectoparasites collected however, were not numerous. Observation and direct examination of the host showed that the ectoparasites didn’t cause any detrimental effects on the hosts. Physiological and ecological factors may have influenced the distribution of ectoparasites on the host.